(untitled) (Herald of Journalism, 2020)
This scientific article describes the advertisement in the tourism sector. Showing its main functions and goals, as well as distinguishing features. Advertising in the modern world is a complex social phenomenon, shag- nuvshee far beyond the kind of employment rights. It also is not just a business, but a much broader phenomenon that covers virtually all aspects of society, including tourism. The tourism industry has its own peculiari- ties, as operates virtually no tangible goods and services. The characteristic features of tourist services are intangibility, inability to storage, exposure to seasonal fluctuations, which in turn updates the advertising space. There- fore, advertising in today’s global world is an integral part of the function- ing of services of tourism.